Are university teachers ready to use and adopt e-learning system? An empirical substantiation during COVID-19 pandemic. Issue 4 (24th August 2021) - Patra, Soumendra Kumar; Sundaray, Bijaya Kumar; Mahapatra, Durga Madhab
Abstract : Purpose: To overcome the spread of the noble coronavirus, the lockdown was imposed on March 25, 2020 by the Government of India which adversely affected the education system in the country and changed the traditional classroom teaching to online teaching. This paper aims to explore the factors encouraging university teachers to use and adopt e-learning systems during the COVID-19 pandemic and to find out the major challenges faced by them in adopting e-learning systems in Odisha, an Indian State. Design/methodology/approach: The population of this study was teachers of different universities in Odisha, India. An online questionnaire was administered to collect data from the teachers of the state who were involved in the e-learning system for taking their online classes during the COVID-19 situation. During the study 610 valid responses were processed for data analysis. The results of the analysis were presented through factor analysis, t -test and structural equation model. Findings: The findings revealed three major factors as user-friendly, convenient and performance encouraged teachers to use and adopt e-learning systems. The results also identified major challenges such as accessibility to the internet, information and communication technologies literacy and skills and technological support, faced by university teachers in adopting e-learning systems. Research limitations/implications: The findings of the study have suggested that the university authorities can develop an effective e-learning system to support their teachers for the continuance of education and learning opportunities. The insights of this study can help the regulatory authorities of higher education to redesign policy and infrastructure for promoting effective e-learning systems. Originality/value: Many studies have been conducted in relation to e-learning during COVID-19. However, this is a unique study that identifies supporting factors and addresses the challenges faced by university teachers in adopting an e-learning system.